2021
DOI: 10.1128/mra.00404-21
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequences of 10 Bacteria from the Marine Pseudoalteromonas Group

Abstract: Here, we report the draft genome sequences of 10 marine Pseudoalteromonas bacteria which were isolated, assembled, and annotated by undergraduate students participating in a marine microbial genomics course. Genomic comparisons suggest that 7 of the 10 strains are novel isolates, providing a resource for future marine microbiology investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In our previous study, we isolated a Pseudoalteromonas strain FDHY-MZ2 (Shi et al, 2022), which showed significantly lower algicidal activity against H. akashiwo compared to FDHY-MQ5. These differences could be associated with the significant differences in the genome specific species of Pseudoalteromonas (Alker et al, 2021). Simultaneously, it is plausible that microbial competition, coupled with its impacts on the co-culture of algicidal bacteria and phytoplankton, might contribute to the observed differential species representation.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we isolated a Pseudoalteromonas strain FDHY-MZ2 (Shi et al, 2022), which showed significantly lower algicidal activity against H. akashiwo compared to FDHY-MQ5. These differences could be associated with the significant differences in the genome specific species of Pseudoalteromonas (Alker et al, 2021). Simultaneously, it is plausible that microbial competition, coupled with its impacts on the co-culture of algicidal bacteria and phytoplankton, might contribute to the observed differential species representation.…”
Section: Discussionmentioning
confidence: 99%